Proceedings of the Workshop on Temporal and Spatial Information Processing - 2001
DOI: 10.3115/1118238.1118247
|View full text |Cite
|
Sign up to set email alerts
|

From temporal expressions to temporal information

Abstract: We present a semantic tagging system for temporal expressions and discuss how the temporal information conveyed by these expressions can be extracted. The performance of the system was evaluated wrt. a small hand-annotated corpus of news messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 5 publications
1
55
0
1
Order By: Relevance
“…Regarding point 2), with the exception of the approach adopted in [17], none of the approaches conducted in NLP (see [16]) and IR consider this kind of textual unit as a temporal expression in itself. This is mainly because the issue of analysing temporal information in texts by a named-entities approach has influenced (and is still influencing) a lot of studies.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding point 2), with the exception of the approach adopted in [17], none of the approaches conducted in NLP (see [16]) and IR consider this kind of textual unit as a temporal expression in itself. This is mainly because the issue of analysing temporal information in texts by a named-entities approach has influenced (and is still influencing) a lot of studies.…”
Section: Related Workmentioning
confidence: 99%
“…Many research projects take more specifically interest in temporal information expressed in texts, designing annotation tagsets that describe their semantics, such as the TimeML project [7]. A challenging task tackled by many research projects is to transform calendar expressions found in texts into a structured and computable format, such as iCalendar or ISO 8601 standards: for instance, they aim at anchoring the situations described in texts on a timeline [8], [9], [10].…”
Section: Related Workmentioning
confidence: 99%
“…Mani [10] gives a good review about the recent trend. Research works in this area can be classified into four types: designing annotation scheme for temporal information representation [4,6,12]; developing temporal ontology which covers temporal objects and their relationships between each other [2,7]; Identifying time-stamps of events or temporal relationships between events [5,9]; Identifying and normalizing temporal expressions from different languages [1,3,8,11,13,15].…”
Section: Related Workmentioning
confidence: 99%